The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1193/121912eqs352m
|View full text |Cite
|
Sign up to set email alerts
|

Loss Estimation of Tall Buildings Designed for the PEER Tall Building Initiative Project

Abstract: As part of the PEER Center's tall building initiative (TBI) project, practicing engineers designed three structural systems, each based on commonly used codes and guidelines in addition to the guidelines developed by PEER. The designs were analyzed by three research teams, using a set of 75 ground-motion pairs, to predict response parameters for evaluating the performance of tall buildings. This study focuses on analytically estimating the seismic losses to these buildings to assess their relative seismic perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The components have been grouped into drift and acceleration-sensitive components in order to relate the component performances and repair costs to the selected EDPs. The repair costs of each category have been normalized by median replacement costs (1192.27 €/m 2 ) for the L'Aquila RC buildings (Di Ludovico et al 2017b), as commonly found in the available literature (Agha Beigi et al 2015, Ramirez et al 2012, Shome et al 2015).…”
Section: Pbee Analysis Of the Case Studiesmentioning
confidence: 99%
“…The components have been grouped into drift and acceleration-sensitive components in order to relate the component performances and repair costs to the selected EDPs. The repair costs of each category have been normalized by median replacement costs (1192.27 €/m 2 ) for the L'Aquila RC buildings (Di Ludovico et al 2017b), as commonly found in the available literature (Agha Beigi et al 2015, Ramirez et al 2012, Shome et al 2015).…”
Section: Pbee Analysis Of the Case Studiesmentioning
confidence: 99%
“…25. It is known that the relative contribution of S and NS repair costs to the total repair cost varies significantly with the seismic intensity level (Shome et al 2015). The repair cost at lower intensities is dominated by NS damage, whereas the same for the S damage becomes significant at higher intensities.…”
Section: Fig24 Random Effects In Loss Resultsmentioning
confidence: 99%
“…PEER methodology is also adopted by the ATC-58 (2011), and uses a Monte Carlo simulation procedure to quantify the performance of different structural facilities. Shome et al (2015) performed loss estimation of tall buildings designed for the PEER Tall Building Initative Project (PEER TBI, 2017). Based on the dollar results, the performance of the dual-system building is compared with the other buildings systems considered in TBI study.…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of variables and their uncertainty as well as their correlations with each other that are briefed in the above paragraph would make the numerical integration of probabilistic loss inconvenient. To this end, Shome et al (2015) propose a Monte Carlo-based simulation approach to compute the exceedance probability of loss for tall buildings by populating the conditional random variables described in the above distributions.…”
Section: Tall Buildingsmentioning
confidence: 99%